Interleukin-11 up-regulates endoplasmic reticulum stress induced target, PDIA4 in human first trimester placenta and in vivo in mice. (May 2017) - Winship, A.L.; Sorby, K.; Correia, J.; Rainczuk, A.; Yap, J.; Dimitriadis, E.
Abstract: Interleukin (IL)11 is a crucial factor for human trophoblast function and placentation. Elevated levels are associated with pregnancy complications including preeclampsia, intrauterine growth restriction (IUGR) and preterm birth. However, the regulation of IL11 in the placenta has not been investigated. We examined the effect of pro-inflammatory cytokines IL1β and TNFα, as well as low oxygen tension (2%) on IL11 levels in first trimester placental villous explants. IL1β upregulated IL11 mRNA and protein, while TNFα and low oxygen had no effect. Using mass spectrometry, we identified protein disulfide isomerase 4 (PDIA4) in IL11-treated first trimester human placental explants (100 ng/ml, 24 h, n = 3), but not PBS control tissues. PDIA4 is a member of the PDI family, also known as endoplasmic reticulum (ER) stress protein (ERP)72. We previously identified GRP78 (a master regulator for ER stress) in human placenta for the first time and demonstrated that IL11 up-regulates GRP78 in the placenta. In this report, we demonstrated that IL11 upregulates PDIA4 protein in human placental villous tissue, HTR8-SVneo trophoblasts (cell line) and in vivo in IL11-treated mouse placenta. We aimed to determine whether IL11 upregulates other ER stress proteins in human first trimester placental villous. IL11 stimulated ERP44, but not GRP94, or PDI. Placental endoplasmic reticulum stress has been postulated in the pathophysiology of preeclampsia and IUGR, but its activation remains elusive. Together, these data suggest that IL11 could trigger an ER stress response in the placenta, which may contribute to obstetric complications such as preeclampsia. Highlights: Interleukin-(IL)11 is regulated by IL1β, but not TNFα, or low oxygen tension placental villous. HPLC MS/MS identified protein disulfide isomerase 4 (PDIA4) in IL11-treated first trimester villous. PDIA4 is an ER stress induced protein. IL11 upregulates PDIA4 protein in human villous, HTR8-SVneo trophoblasts and in vivo in IL11-treated mouse placenta.